A web tool for generating user-interface interactive networks - WenJun Zhang (International Academy of Ecology and Environmental Sciences, 2021)
In the present study, an online web tool (http://www.iaees.org/publications/software/netJa/netGen.htm) for generating user-interface interactive networks was presented. In the network, the user can mouse-press any of the nodes to drag the network, examine network topology, evaluate node centrality, etc. It can be freely used and run on popular web browsers as Chrome, etc.